Rusia: manifestaciones ciudadanas en una autocracia electoral. Las protestas de 2019 en Moscú - Chaguaceda, Armando; González, Claudia (El Colegio de México A.C., 2020)
In 2019, Moscow saw political demonstrations as a result of the authorities’ blocking of the registration of opposition candidates for the local elections in Moscow. As the culmination of a series of citizen protests around different causes that spread throughout the country, these protests presented a real challenge to the political regime. Their context, evolution and possible implications are analyzed in this paper, both in correlation with the methods of “managed democracy” within Russia’s regime of electoral autocracy, as well as with the perfecting of technological tools in light of two consequences: political pluralism and constraints on civic practice.